Profil Pengkajian Resep Racikan Pediatri Di Puskesmas Salotungo Kabupaten Soppeng Periode Januari-Maret 2022 - Gina Nurnasyah; Ririn; Aztriana (CV. Multi Kreasi Media, 2023)
Prescription review is an activity in pharmaceutical services that begins with the selection of administrative requirements, pharmaceutical requirements and clinical requirements for both inpatients and outpatients. The prescription review aims to analyze drug-related problems and avoid medication errors, especially at the prescribing stage. This research is a non-experimental research with a descriptive research design. Data collection was carried out using a retrospective approach. The population in this study were all prescriptions for pediatric concoctions at the Salotungo Health Center Soppeng Regency for the period January-March 2022 which met the inclusion criteria of 159 prescriptions. The results showed the percentage of administrative aspects completeness, namely patient name (100%), patient age (100%), patient gender (100%), patient weight (88.67%), doctor's name (95.59%), initials doctor (96.85%), date of prescription (99.37%), room of prescription unit (99.37%). Compatibility of pharmaceutical aspects, namely dosage form (93.71%), dosage strength (0%), drug dosage (100%), drug amount (100%), rules and method of use (100%), hygroscopic instability (37.33% ), photolytic instability (66.65%), incompatibility (0%). Then for the clinical aspect, namely there is no drug duplication, for dosage accuracy there are 2% experiencing an overdose and (3%) experiencing an underdosage. It can be concluded that from all the aspects that have been studied at the Salotungo Health Center, Soppeng Regency, they have not fully complied with the suitability of the prescription based on the Regulation of the Minister of Health of the Republic of Indonesia No. 74 of 2016 concerning Standards for Pharmaceutical Services at Health Centers.